Development of a Conceptual Model of Emotional Literacy Education in Preschool Children Using an Integrative Development–Emotional Approach - Heidari Nia, Mahnaz (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to design a comprehensive conceptual model of emotional literacy education for preschool children based on an integrative developmental–emotional framework. Methods and Materials: This study employed a qualitative research design conducted in preschool educational settings in Tehran, Iran. Participants were selected through purposive sampling with maximum variation and included preschool teachers, administrators, child psychologists, developmental psychologists, educational counselors, and curriculum specialists. Data were collected using semi-structured in-depth interviews, focus group discussions, and systematic document analysis of preschool curricula and emotional education guidelines. Data analysis followed thematic analysis with grounded theory procedures, including open, axial, and selective coding, supported by constant comparative analysis. Trustworthiness was ensured through prolonged engagement, member checking, peer debriefing, and maintenance of an audit trail. Findings: The analysis produced an integrative conceptual model structured around sequential developmental-emotional domains including emotional awareness, emotional expression, emotion regulation, empathy development, social interaction skills, and consolidation of competencies across contexts. The findings demonstrated that emotional literacy develops through dynamic interactions among instructional inputs, relational pedagogy, peer socialization processes, contextual moderators, and family–school continuity. Emotion regulation emerged as a central mechanism linking emotional understanding with social competence, while environmental and relational conditions were identified as critical moderators of effectiveness. Conclusion: The proposed model provides a coherent theoretical and practical framework for advancing emotional literacy education in preschool children and offers clear implications for curriculum design, teacher training, and early childhood educational policy.